Evaluation of Flavonoid Derivative and Doxorubicin Effects in Lung Cancer Cells (A549) Using Differential Pulse Voltammetry Method - Mohammad Amjadi; Jalal Mohammadi Khoshraj; Mir Reza Majidi; Behzad Baradaran; Miguel de la Guardia (Tabriz University of Medical Sciences, 2018)
Purpose: Electrochemical measurements have prompted the progress as a consequence of their affectability, cost-affectivity and comparatively short examination time. The aim of this study was the fast evaluation of the effect of chemotherapy compounds on the viability of lung cancer cells (A549) via electrochemical methods. Methods: Cyclic voltammetry (CV) was used as a primary method to distinguish between electrochemical behavior of normal and lung cancer cells. Differential pulse voltammetry (DPV) was employed as a complementary analyses method for the impact of doxorubicin (DOX) and Flavonoid modified drug (FMD) (US patent Application number: 62548886) on Lung cancer cells. Results: Only one oxidative peak, at approximately -0.15 V was detected through DPV method in cancer cell line. While a significant distinguish was not seen in CV. The current intensity (I) was decreased in cancer cells with increasing the DOX and FMD levels (t=99.027, α=0.05, P=0.0000), (t=135.513, α=0.05, P=0.0000), respectively. Conclusion: The movement of cancerous cells towards death through chemotherapy drugs such as DOX and FMD can make distinct and significant changes in the electrochemical behaviors of those cells.